Students' Perception of The Free Nutritional Meal Program and Its Impact on Attendance Motivation - Samosir, Octavianus; Trivena Gracia Sirait; Rika Budiarti; Gabriella Pardede; Evi Melinda Sipayung; Gloria Sirait (CV Putra Publisher, 2026)
Free nutritious meal program, learning motivation, student nutrition, education, government policy The Free Nutritious Meal Program (MBG) is a strategic government initiative designed to improve the quality of education by meeting the nutritional needs of students fairly and equitably, especially for children from low-income groups. This study aims to analyze the impact of the MBG program implementation on student academic motivation at SMP Negeri 8 Pematangsiantar. The method used is a mixed method approach that combines a comprehensive literature review with empirical data collection through attendance monitoring and semi-structured interviews involving students in grades 9-8 (n=28) during the period July-December 2024. The findings indicate that the MBG initiative substantially increased student learning motivation, as reflected in consistently high attendance rates (average 99.97%), increased learning concentration, enthusiasm for learning, and better social interactions within the school environment. However, the implementation of this program faces various obstacles including unequal distribution, budget constraints, minimal cross-sector coordination, and variations in student satisfaction regarding the quality and taste of the menu provided. Therefore, a strong oversight mechanism, comprehensive technical regulations, and integrated policy synergy are needed to ensure the sustainability and effectiveness of the program